The ISU-ISU KEMISKINAN, PENDIDIKAN, DAN GLOBALISASI - EKA MUSTIKA RIANTINA; YOSE RIZAL FAJRI; ANITA MAULIYANTI; DANI ATMAJA (Raudhah - Proud To Be Professional, 2022)
Abstract:Poverty in education and globalization is a series that is related to each other. The researcher will raise issues regarding issues of educational poverty and globalization. Researchers conduct research in libraries or can be referred to as Library Research. Research in the library is intended to search for literature books, documents or official reports, articles, magazines, journals, bulletins, and research results related to this research. The results of this study indicate that educational issues include loss learning, lack of motivation to learn during the pandemic, non-optimal aspects of self-regulated learning, changes to the curriculum for independent learning, and government domination in education development without involving the community.Globalization issues include digital transformation, three new literacys (data literacy, ICT, and humans), metaverse, and the trend of the gaming industry to the realm of sports and their impact on education.